1993
DOI: 10.1007/bf02353716
|View full text |Cite
|
Sign up to set email alerts
|

Residential versus day treatment for children: A long-term follow-up study

Abstract: Adults and adolescents, who as children, received day or residential treatment were followed up ten years after treatment completion. No differences were found between the two treatment modalities on follow-up ratings of personal and social adjustment. This pattern was not influenced by gender, IQ, or presenting problem. Overall, about two-thirds of the children demonstrated improvement at follow-up. As expected, individuals demonstrating higher levels of personal and social adjustment at initial assessment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
0
7
1
Order By: Relevance
“…While these narratives are encouraging, several youth in our study, as well as subsets of youth in other studies (Davidson-Methot, 2004;Erker et al, 1993;Gilman & Barry, 2003), failed to report improved functioning and increased life satisfaction post-discharge. It is possible that, despite overall improvements, some youth in RT and IHT continue to function at a low level.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…While these narratives are encouraging, several youth in our study, as well as subsets of youth in other studies (Davidson-Methot, 2004;Erker et al, 1993;Gilman & Barry, 2003), failed to report improved functioning and increased life satisfaction post-discharge. It is possible that, despite overall improvements, some youth in RT and IHT continue to function at a low level.…”
Section: Discussioncontrasting
confidence: 64%
“…Several studies suggest that youth fare poorly after treatment (e.g., Davidson-Methot, 2004;Erker, Searight, Amanat, & White, 1993), while other investigations reveal short-term benefits (e.g., Peterson & Scanlan, 2002). In a recent meta-analysis, Knorth, Harder, Zandberg, and Kendrick (2008) concluded that there is evidence of improvement in psychosocial functioning for children and adolescents after a period of residential care, especially for youth with externalizing disorders.…”
Section: Abstract Intensive Mental Health Services Youth Perceptionsmentioning
confidence: 96%
“…Moreover, as part of a continuum of care shorter residential stays can contribute to long-term gains. Notably, the findings of Erker et al (1993) and Wilmshurst (2002) suggest that day programs which include intense family involvement are a potentially less intrusive alternative as long as families are able and willing to keep the child or adolescent at home.…”
Section: The Importance Of Family Involvementmentioning
confidence: 96%
“…Three studies in particular address a number of previous methodological flaws and provide persuasive evidence. Erker, Searight, Amanat, and White (1993) conducted interviews to compare the social and emotional outcomes of 61 children at least 10 years after they had received day (n = 45) or residential treatment (n = 16) in a private facility. The ages of the children at admission ranged from 4 to 11 years, whereas the range at follow-up was between 13 and 27 years of age.…”
Section: The Importance Of Family Involvementmentioning
confidence: 99%
“…In a study of the outcomes of severely disturbed adolescents receiving intensive, short-term residential treatment, improvements in standardized measures of symptom severity, functioning, and psychosocial adaptation were noted at three months post-discharge, but there were no changes in these measures between three and 12 months post-discharge (Leichtman, Leichtman, Barber, & Neese, 2001). In a 10-year follow up of children discharged from residential (n = 16) and day (n = 45) treatment, two-thirds of the children were deemed to have shown improvement at follow up based on nonstandardized measures of social and personal adjustment; however, these children were less well-adjusted 10 years later as compared to children with presenting symptoms of mild intensity (Erker, Searight, Amanat, & White, 1993). However, in few studies have the long-term outcomes (beyond 2 years) using standardized measures for children discharged from RTC been reported.…”
mentioning
confidence: 85%